2008
DOI: 10.1371/journal.pone.0002940
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1 Trial of AMA1-C1/Alhydrogel plus CPG 7909: An Asexual Blood-Stage Vaccine for Plasmodium falciparum Malaria

Abstract: BackgroundApical Membrane Antigen 1 (AMA1), a polymorphic merozoite surface protein, is a leading blood-stage malaria vaccine candidate. This is the first reported use in humans of an investigational vaccine, AMA1-C1/Alhydrogel, with the novel adjuvant CPG 7909.MethodsA phase 1 trial was conducted at the University of Rochester with 75 malaria-naive volunteers to assess the safety and immunogenicity of the AMA1-C1/Alhydrogel+CPG 7909 malaria vaccine. Participants were sequentially enrolled and randomized withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
119
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 103 publications
(129 citation statements)
references
References 31 publications
10
119
0
Order By: Relevance
“…However, these two studies did not address whether C1L was the only critical region for antibodies other than AMA1-3D7 and AMA1-FVO antibodies. When U.S. adults were immunized with AMA1-C1, which is a mixture of AMA1-3D7 and FVO, the purified IgGs showed inhibitory activity against 3D7 and FVO parasites, as judged by GIA, as expected, but their activity was much less than their activity against L32 and M24 parasites (11). The data suggested that there may be other critical sites which are not covered by either 3D7 or FVO.…”
Section: Figsupporting
confidence: 52%
See 1 more Smart Citation
“…However, these two studies did not address whether C1L was the only critical region for antibodies other than AMA1-3D7 and AMA1-FVO antibodies. When U.S. adults were immunized with AMA1-C1, which is a mixture of AMA1-3D7 and FVO, the purified IgGs showed inhibitory activity against 3D7 and FVO parasites, as judged by GIA, as expected, but their activity was much less than their activity against L32 and M24 parasites (11). The data suggested that there may be other critical sites which are not covered by either 3D7 or FVO.…”
Section: Figsupporting
confidence: 52%
“…Indeed, there is evidence of balancing selection in domains I and III in field parasites from Nigeria (7), Papua New Guinea (8), Thailand (9), and Kenya (10). We and other investigators have conducted multiple phase 1 trials of AMA1 using AMA1-3D7, AMA1-FVO, or a mixture of both (AMA1-C1), and the antibodies induced by the vaccines showed strain-specific functional activities, as judged by the in vitro growth inhibition assay (GIA; also referred to as the invasion inhibition assay [IIA]) (11)(12)(13)(14). Only two phase 2 field trials with AMA1 vaccines have been conducted, and neither of them showed significant clinical protection in a target population of African children (15,16).…”
mentioning
confidence: 99%
“…Furthermore, no signs of systemic toxicity were observed after single or repeated administrations of the malaria candidate vaccines formulated with AS01 or AS02 Adjuvant Systems in rabbits (Segal et al ., 2015). CpG ODNs have been tested as adjuvants in a number of non‐clinical and phase I–III clinical trials testing vaccines against infectious diseases (Cooper et al ., 2004a,2004b; Klinman et al ., 2006; Mullen et al ., 2008) and cancer (Brody et al ., 2010; Pilon‐Thomas et al ., 2006; Speiser et al ., 2005; Valmori et al ., 2007). In previous studies in non‐human primates or in humans, no significant toxicities were reported after injections of CpG 7909 even at high doses (Krieg et al ., 2004; Stewart et al ., 2008).…”
Section: Discussionmentioning
confidence: 99%
“…68 Results from clinical studies using recombinant P. falciparum AMA1-C1/Alhydrogel plus CpG 7909 vaccine showed 14-fold-higher AMA1-specific IgG with significantly increased in vitro growth inhibitory activity against homologous parasites compared to AMA1/Alhydrogel alone. 69 Thus, TLR 9 agonists are effective immunomodulatory molecules for use as vaccine adjuvants.…”
Section: Adjuvant Designmentioning
confidence: 99%
“…As with adjuvants used with protein-based vaccines, adjuvants for gene-based vaccines require extensive safety evaluation. After nonclinical studies indicated that the oligonucleotide CPG 7909 significantly enhanced the immunogenicity of the recombinant protein-based malaria vaccine, AMA1-C1, 234,235 subsequent clinic testing raised concerns regarding the frequency of allergic reactions 69 and this in turn led to identification and testing of less allergenic formulations. 236 A major step in establishing safety of immunomodulatory adjuvant systems occurred with the co-administration of plasmids encoding human GM-CSF to healthy adults as an immunostimulant to improve the potency of the pentavalent MuStDO5 malaria vaccine (a mixture of five plasmids encoding pre-erythrocytic stage antigens).…”
Section: Safety Of Molecular Vaccinesmentioning
confidence: 99%